The Assistance in Human Resource Management and Implementation of Accounting Software in Palm Oil Plantation Business Units - Hasrita Lubis; Siti Aisyah Nasution; Anggono; Melinda Siregar; Siti Dini; Hendra Nazmi; Annisa Nauli Sinaga (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2026)
The palm oil plantation sector plays a strategic role in Indonesia's economy; however, many plantation business units still face challenges in human resource (HR) management and financial administration. Limited employee competencies, inadequate performance management systems, and the continued use of manual accounting practices often reduce operational efficiency and the accuracy of financial reporting. To address these issues, a community service program was conducted in the form of assistance and socialization on HR management and the implementation of Accurate accounting software for employees of PT. Kallista Alam. The program employed a participatory training approach that combined theoretical explanations, discussions, demonstrations, and hands-on practice. The activities focused on enhancing participants’ understanding of effective HR management, introducing the accounting cycle, and providing practical training in the use of Accurate software for financial recording and reporting. The results indicated that participants gained a better understanding of HR management practices and improved their knowledge of digital accounting systems. The program also increased participants’ awareness of the importance of technology adoption in supporting accurate, efficient, and transparent financial management. Overall, the assistance program contributed to strengthening employee competencies and promoting the adoption of accounting software to improve organizational performance and competitiveness in the palm oil plantation industry.